(untitled) (JURNAL PESISIR DAN LAUT TROPIS, 2023)
Seagrass is the main component of the seagrass bed ecosystem. The existence and productivity of seagrass beds have a very important ecological role for life in the sea and on land. This research is to determine the type of seagrass, to determine the condition and structure of the seagrass community and environmental parameters on the coast of Basaan Satu Village. The method that the author uses is the quadratic transect method. This method is usually used to observe the community structure of seagrass beds using a line transect of 50 m and a square of 50×50 cm². Seagrass species identified in the coastal waters of Basaan Satu Village, Ratatotok District, Southeast Minahasa Regency, namely as many as 5 species including Syringodium isoetifolium, Thalassia hemprichii, Halodule uninervis, Halodule pinifolia, Enhalus acoroides and cymodocea rotundata. Seagrass cover per species was dominated by the species Syringodium isoetifolium, the highest density was for the species Syringodium isoetifolium, the highest important value index for seagrass was found for the species Thalassia hemprichii with a value of 102.26%, the diversity index value was 0.93 which was classified as moderate, and the index value dominance is equal to 0.53. low category. Environmental parameters of seagrass beds at the study site have a range of values: temperature 31.47-33.39°C, salinity 29.08-30.49 ppt, dissolved oxygen 6.55-9.67, pH 9.23- 9.94, turbidity 0-2.6, and the substrate found was sand, muddy sand, crushed coral sand, and coral rubble. Keywords: Seagrass Conditions, Community Structure, Basaan Satu Village ABSTRAK Lamun merupakan komponen utama penyusun ekosistem padang lamun. Keberadaan dan produktivitas padang lamun memiliki peranan ekologi yang sangat penting bagi kehidupan di laut maupun di darat. Penelitian ini Untuk mengetahui jenis lamun, Untuk mengetahui kondisi dan struktur komonitas padang lamun dan parameter lingkungan di pantai Desa Basaan Satu. Metode yang penulis gunakan yaitu metode transek kuadrat. Metode ini biasanya di pakai untuk mengamati struktur komunitas padang lamun menggunakan line transek 50 m dan kuadrat 50×50 cm². Spesies lamun yang teridentifikasi di perairan pantai Desa Basaan Satu Kecamatan Ratatotok Kabupaten Minahasa Tenggara, yaitu sebanyak 5 spesies diantaranya sebagai berikut Syringodium isoetifolium, Thalassia hemprichii, Halodule uninervis, Halodule pinifolia, Enhalus acoroides dan cymodocea rotundata. Tutupan lamun per jenis didominasi oleh spesies Syringodium isoetifolium, kepadatan jenis tertinggi pada spesies Syringodium isoetifolium, Indeks nilai penting lamun tertinggi terdapat pada spesies Thalassia hemprichii dengan nilai sebesar 102,26%, nilai indeks keanekaragaman yaitu 0,93 yang tergolong sedang, dan nilai indeks dominasi yaitu sebesar 0,53. kategori rendah. Parameter lingkungan perairan padang lamun yang berada di lokasi penelitian memiliki kisaran nilai: suhu 31,47-33,39°C, salinitas 29,08-30,49 ppt, Oksigen terlarut 6,55-9,67, pH 9,23-9,94, kekeruhan 0-2,6, dan substrat yang ditemukan pasir, pasir berlumpur, pasir pecahan karang, pecahan karang. Kata Kunci: Kondisi lamun, Struktur Komunitas, Desa Basaan Satu